Protection of Creditor Rights of Collateral Holders in PKPU: a Study on the Rejection of Settlement Agreements - Indah Kusumaningrum (International Journal Labs, 2026)
This study analyzes how the rights of creditors who hold guarantees in the PKPU process are affected by the rejection of the peace agreement. This research was prepared using juridical doctrinal research methods and legal comparisons between the provisions in Law Number 37 of 2004 concerning Bankruptcy and PKPU in Indonesia and the Companies' Creditors Arrangement Act in Canada. The right of creditors of the guarantor in PKPU who reject the peace agreement as mentioned in Article 281 paragraph (2) of Law Number 37 of 2004 concerning Bankruptcy and PKPU is stated to receive compensation equal to the lowest value among the value of the collateral in the collateral document or the value of the collateral object determined by the appraiser appointed by the Supervisory Judge or the actual value of the loan. However, there are no further arrangements regarding the mechanism, period and legal consequences for the application or violation of these provisions, thus creating a legal vacuum and potentially harming the right of the creditor to obtain compensation. Furthermore, the creditors of the guarantor also cannot or at least have difficulty executing the object of the guarantee to obtain repayment of receivables against the debtor. On the other hand, in the restructuring process through the Companies' Creditors Arrangement Act in Canada, the creditor of the guarantor may execute the object of the guarantee with the approval of the judge if it does not approve the restructuring plan submitted by the debtor and can prove that the debtor no longer has the ability to carry out the restructuring plan and the debtor is unable to carry out its debt payment obligations to creditors. This can be conveyed by submitting an application to the court to lift the stay period to execute the object of the guarantee. In the end, this study proposes a form of further regulation of Article 281 paragraph (2) of Law Number 37 of 2004 concerning Bankruptcy and PKPU, which is at least in the form of a Government Regulation to regulate the mechanism, period, and legal consequences of the provision of compensation from debtors for creditors who reject the peace plan in the PKPU process.